2017
DOI: 10.24200/sci.2017.4047
|View full text |Cite
|
Sign up to set email alerts
|

Effects of non-equilibrium condensation on aerodynamics of the flow field in a steam turbine cascade

Abstract: Abstract. In the present paper, an in-house CFD code is developed using Roe scheme to simulate a condensing two-phase ow in blade to blade passage of a steam turbine. E ects of condensation on the ow eld of steam turbine rotor tip section are investigated for di erent outlet pressures. Firstly, comparison is performed between results of wet and dry cases. Then, e ects of outlet pressure variations on the ow eld are studied. Finally, e ects of condensation on di erent speci cations of the ow eld (total pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…But the losses value was overestimated due to the neglect of the wetness fraction. By the numerical investigation of Bagheri-Esfe [16] and Vatanmakan [17] for the condensing steam flow through turbine blades, it is shown that the entropy generation induced by non-equilibrium condensation can reduce the steam turbine efficiency and the large heat flux can reduce entropy generation.…”
Section: Introductionmentioning
confidence: 99%
“…But the losses value was overestimated due to the neglect of the wetness fraction. By the numerical investigation of Bagheri-Esfe [16] and Vatanmakan [17] for the condensing steam flow through turbine blades, it is shown that the entropy generation induced by non-equilibrium condensation can reduce the steam turbine efficiency and the large heat flux can reduce entropy generation.…”
Section: Introductionmentioning
confidence: 99%
“…Bagheri-Esfe et al. 31,32 studied the influence of nonequilibrium condensation on the efficiency and deflection angle of steam turbine stages under subsonic, transonic, and supersonic conditions, and compared and analyzed the aerodynamic characteristics of steam turbines in the NES and noncondensation models. Condensation had a great influence on the expansion and Mach number of the steam turbine under supersonic condition.…”
Section: Introductionmentioning
confidence: 99%